Abandonment of housing projects in Malaysia: contributory factors and effects on purchasers / Nur Hanisa Zulkifli - Zulkifli, Nur Hanisa (Faculty of Law, 2012)
The problem of delay in the construction industry is a national issue in Malaysia. The main purpose of this study is to identify the causes of house abandonment in Malaysia and its effect on the house buyers. This study takes an integrated approach and attempt to analyse the causes and consequences in detail. The interview was held with the officer of Ministry of Housing and Local Government, officer from Malaysia Building Society Bhd (MBSB), bank, developer and victims of house abandonment to identify the real factors of house projects being abandoned. The achievement of this paper would be to provide a better solution or recommendations to curb the issue. It is hope with this research; it will benefit the students, researchers and local authority.